Rodinný dům - Hofrichter, Michal (České vysoké učení technické v Praze, 2025)
Předmětem bakalářske práce je vypracovat architektonickou studii na návrh rodinného domu ve stupni pro stavební povolení. Zadáním je členitá a tvarem charakteristická parcela, která se nachází na Barrandově v městské části Praha 5. Orientována na severovýchodním svahu barrandovských skal s výhledem do Prokopského údolí. Hlavní myšlenkou projektu bylo harmonické zachovaní severních výhledů do údolí a okolní Prahy, otevřít obytnou část domu do jižní zahrady a plynule propojit interiér s exteriérem. Dům tak bude nabízet uživatelům příjemné bydlení v jedné z nejatraktivnějších lokalit Prahy.

The subject of the bachelors thesis is to develop an architectural study for the design of a family house at the level required for a building permit. The assignment concerns a plot with a distinctive shape and articulation, located in Barrandov, a district of Prague 5. It is situated on the northeastern slope of the Barrandov cliffs, offering views into the Prokopské Valley. The main concept of the project was to harmoniously preserve the northern views of the valley and the surrounding Prague, to open the living area of the house toward the southern garden, and to seamlessly connect the interior with the exterior. The house will thus offer its users comfortable living in one of the most attractive locations in Prague.
Family House
Keywords: rodinný dům; rodinné bydlení; bakalářská práce; Barrandov; architektonická studie; family house; family living; bachelor's thesis; Barrandov; architectural study